Suction assisted pulse lavage: randomised controlled studies comparing its efficacy with conventional dressings in healing of chronic wounds. Issue 1 (3rd September 2012) - Shetty, Rahul; Barreto, Elvino; Paul, Kingsly M
<x xml:space="preserve">Abstract</x> Chronic, open, non‐healing wounds pose a continual challenge in medicine as the treatment is variable and there are no documented consistent responses. Although wound aetiologies vary and there are a number of factors that affect chronic wound pathogenesis, wound ischaemia and bacterial colonisation of wounds are the chief concerns among them. Conventionally, pulse lavage has been used primarily as a wound debriding device. To address both the critical factors of wound ischaemia and bacterial burden, a couple of technical points were proposed and applied in this study. The objective of our study was to evaluate pulse lavage therapy's ability to improve the healing rate of chronic wounds compared to that of the traditional saline‐wet‐to‐moist dressings. The study period was from 1 August 2010 to 31 January 2012 and was conducted in our institution. Thirty patients with 31 chronic, non‐healing wounds were enrolled in the study after obtaining proper consent. Subjects were randomised (15 patients each) to the pulse lavage group and the control group. Patients in the test group were subjected to irrigation of their wounds with pulsed lavage at 10 to 15 psi pressure. In the control group, wound was closed by applying moist betadine saline gauze dressings after cleaning with saline. Wounds treated with pulse lavage system significantly reduced in size, had better control of bacterial contamination and had overall faster healing rates. Efficacy of pulse lavage can be increased by correct method of administration of the irrigant.